2021
DOI: 10.1186/s12875-021-01371-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing interventions to reduce antibiotic use: a qualitative study in high-prescribing practices

Abstract: Background Trials have shown that delayed antibiotic prescriptions (DPs) and point-of-care C-Reactive Protein testing (POC-CRPT) are effective in reducing antibiotic use in general practice, but these were not typically implemented in high-prescribing practices. We aimed to explore views of professionals from high-prescribing practices about uptake and implementation of DPs and POC-CRPT to reduce antibiotic use. Methods This was a qualitative focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Given that much existing qualitative research with healthcare professionals about AMS strategies was within trials and unspecific to implementation or high-prescribing practices, we conducted our own qualitative research. The methods of this focus group study are reported in detail elsewhere [ 26 ]. In brief, we held nine focus groups with 50 professionals (3–11 per practice) in high-prescribing practices (i.e.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that much existing qualitative research with healthcare professionals about AMS strategies was within trials and unspecific to implementation or high-prescribing practices, we conducted our own qualitative research. The methods of this focus group study are reported in detail elsewhere [ 26 ]. In brief, we held nine focus groups with 50 professionals (3–11 per practice) in high-prescribing practices (i.e.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Influences on antibiotic prescribing: We fully report the identified influences on antibiotic prescribing and optimisation in our review of qualitative studies in the UK [ 34 , 35 ], our focus group study in high-prescribing practices [ 26 ] and in Supplementary File 1 . From these, we selected influences considered important, modifiable by an intervention and most feasible to address.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that deprived and ethnic minority populations were perceived as needing more antibiotics, as clinicians consider the wider context of patients' lives, such as their (perceived) ability to self-care, reconsult if needed, risk of complications, and the impact of not working. This illustrates the role of perceptions of general practice clinicians in considering and treating patients holistically [25]. Participants also suggested that higher prescribing might be more likely in situations when explaining non-prescribing decisions to patients is difficult, for example, due to cultural understandings and spoken languages.…”
Section: Comparison With the Literaturementioning
confidence: 96%